Research Trends on Pillared Interlayered Clays (PILCs) Used as Catalysts in Environmental and Chemical Processes: Bibliometric Analysis - Macías Quiroga, Iván F. (2022)
Over the last four decades, a large number of studies have been published on pillared interlayered clays (PILCs) used as adsorbent materials and catalysts or supports for transition metals in heterogeneous catalysis. Particularly, PILCs have been used for water treatment through advanced oxidation processes (AOPs) to remove organic pollutants. They have also been studied in various chemical and environmental processes. Because of the growing interest in PILCs, this article is focused on analyzing scientific publications such as research/review articles and book chapters from the last four decades (from 1980 to 2019) through a bibliometric analysis (BA) to visualize and describe research trends on PILCs. By narrowing the bibliographic search to titles, keywords, and abstracts of publications related to PILCs, using Scopus and Web of Science (WoS) (the two scientific databases), a total of 3425 documents have been retrieved. The bibliometric dataset was analyzed by VantagePoint®. The main research trends identified in the last four decades were the use of PILCs in environmental processes (34.4% of total publications) along with chemical processes (petrochemical reactions 17.5%, SCR NOx 10.8%, and decomposition 8.2%). In environmental processes, PILCs have been used in photo-oxidation (32%), CWPO (21.1%), and heterogeneous catalysis (19.4%). Phenols, dyes, and VOCs have been the main pollutants studied using PILCs as catalysts. Fe, Ti, Zr, Cu, and Co are the most supported active phases in PILCs. Other research trends grouped by characterization techniques, countries, research areas, institutes, scientific journals that have published the most on this topic, number of publications per 5-year period, and most frequently used keywords through the last four decades have been identified. It was determined that the number of publications on PILCs has increased since 1980 and the countries with the highest number of publications are China, Spain, and The United States of America.